Centrifuge modeling and numerical analysis on lateral performance of mono-bucket foundation for offshore wind turbines. (1st September 2022) - Wang, Xuefei; Li, Deming; Li, Jiale
Abstract: The lateral loading performance of the mono-bucket foundation for offshore wind turbines is investigated in this study through a series of centrifuge tests and numerical analysis. Six mono-bucket models are considered to assess the influences of aspect ratio under the ultimate condition. The FE model is validated against the centrifuge test results, and the failure mechanism of the foundation is revealed. The parametric study and sensitivity analysis of the soil parameters are performed in the numerical simulations. A modified theoretical calculation method is proposed to estimate the ultimate lateral capacity of the suction bucket foundation by solving the limit equilibrium equations. A correction term is added in the calculation using the "m" method. The position of the rotation center is calculated, demonstrating a better accuracy compared to the previously reported geometric method. The modified calculation method is verified against the field test, the centrifuge test, and the laboratory test. The method is proved to be applicable in estimating the lateral performance of the mono-bucket foundation in a general form. This study aims to provide well-documented data and design references for practical engineers. Highlights: A series of centrifuge tests are performed to assess the ultimate lateral capacity of the suction bucket foundation. The influence of bucket aspect ratio is studied through the experiments and FE model. A modified calculation method is proposed to estimate the ultimate capacity and the position of the rotation center. The proposed method is validated against the field and laboratory tests, demonstrating good accuracy.